Cross-Sectional Study of the Prevalence of Cobalamin Deficiency and Vitamin B12 Supplementation Habits among Vegetarian and Vegan Children in the Czech Republic - Světnička, Martin; Sigal, Anat; Selinger, Eliška; Heniková, Marina; El-Lababidi, Eva; Gojda, Jan (Nutrients, 2022)
Vegetarian (VG) and vegan (VN) diets in childhood are of growing interest due to their perceived health and environmental benefits. Concerns remain due to the possible disruption of healthy growth and development of children because of the scarcity of evidence-based studies. Among the nutrients of special concern is vitamin B12. Therefore, the Czech Vegan Children Study (CAROTS) decided to examine the relationship between B12 metabolism parameters and B12 intake through diet and supplementation. We analyzed laboratory parameters within n = 79 VG, n = 69 VN, and n = 52 omnivores (OM) children (0−18 years old). There were no significant differences in levels of holotranscobalamin (aB12), folate, homocysteine (hcys), or mean corpuscular volume. However, there was a significant difference in levels of cyanocobalamin (B12) (p = 0.018), even though we identified only n = 1 VG and n = 2 VN children as B12 deficient. On the other hand, we identified n = 35 VG, n = 28 VN, and n = 9 OM children with vitamin B12 hypervitaminosis (p = 0.004). This finding was related to a high prevalence of over-supplementation in the group (mean dose for VG 178.19 ± 238.5 µg per day; VN 278.35 ± 394.63 µg per day). Additionally, we found a significant (p < 0.05) difference between B12, aB12, and hcys levels of supplemented vs. non-supplemented VG/VN children. This can show that the intake of vitamin B12 via diet in the VG group might not be sufficient. Secondly, we analyzed a relation between supplement use in pregnancy and breastfeeding and its impact on vitamin B12 levels of children aged 0−3 years. Out of n = 46 mothers, only n = 3 (e.g., 6.5%) were not supplemented at all. We have not identified any clinical manifestation of B12 deficiency and only n = 1 child with low serum cobalamin, a child who did not receive vitamin B12 supplementation and whose mother took only low doses of vitamin B12 (25/µg/day).To conclude, we did not observe any life-threatening or severe consequences of laboratory-stated vitamin B12 deficiency; thus, our group was well supplemented. On the other hand, we have identified many subjects with vitamin B12 hypervitaminosis of unknown impact on their health. Further research and new guidelines for B12 supplementation among VG and VN children are needed.
Keywords: Vegetarians; Cross-Sectional Studies; Prevalence; children; těhotenství; Vitamin B 12 Deficiency; kojenec; vegetarian; mladiství; Česká republika; vitamin B 12; potravní doplňky; prevalence; Infant; B12 supplementation; průřezové studie; zvyky; vegan; Czech Republic; dítě; Vegans; Child; Infant, Newborn; Child, Preschool; deficiency; Habits; ženské pohlaví; novorozenec; vegetariáni; předškolní dítě; Humans; Pregnancy; Vitamin B 12; Dietary Supplements; Female; vegani; Adolescent; vitamin B12; nedostatek vitaminu B12; lidé